Levocabastine eye drops are effective and well tolerated for the treatment of allergic conjunctivitis in children - Brunello Wüthrich; Martin Gerber (Hindawi Limited, 1995)
This open-label, prospective, multicentre, 4-week trial was undertaken to assess the efficacy and tolerability of twice daily levocabastine eye drops (0.5 mg/ml), with sodium cromoglycate nasal spray for the relief of concurrent nasal symptoms if required, in a total of 233 children with seasonal allergic conjunctivitis. No correlation between efficacy, tolerability and age was found. Investigator assessments revealed that the total severity of ocular symptoms decreased by 84 ± 34% in patients < 12 years and 85 ± 30% in those ≥ 12 years, with corresponding reductions in the total severity of ocular findings of 84% in both patient groups over the 4-week treatment period. Global assessments of therapeutic efficacy revealed the effect of therapy on ocular symptoms to be excellent or good in 81% of patients < 12 years and 82% of those ≥ 12 years after 2 weeks of treatment, with corresponding values at the end of the trial of 88% and 82% in the two groups, respectively. Treatment tolerability was considered to be excellent or good by 94% of patients overall. Application site reactions were the most common adverse event associated with ocular levocabastine, occurring in 13% of patients < 12 years and 9% of those ≥ 12 years. Twice daily levocabastine eye drops therefore appear to be effective and well tolerated for the treatment of seasonal allergic conjunctivitis in children.